Nuclear and Cytoplasmic Expression of ErbB-4 in Prostate Cancer - Ben-Yosef, R.; Sarid, D.; Vexler, A.; Lidawi, G.; Inbar, M.; Marmor, S.; Starr, A.; Hahoshen, N. Yaal (The International journal of biological markers, 2007)
To evaluate cytoplasmic and nuclear ErbB-4 expression in prostate cancer specimens and its association with outcome. Specimens of 50 prostate cancer patients were investigated for ErbB-4 overexpression using Immunohistochemistry staining. Cytoplasmic and nuclear staining was graded as 0-3 according to its intensity. The prognostic parameters were tumor stage, PSA level, Gleason score, probability of positive lymph nodes (Partin's tables and Roach equation), and 5-year disease free survival (Kattan nomogram). Overexpression of ErbB-4 (> or = 1) was detected in 30 (60%) patients and overexpression using cytoplasmic and nuclear staining was > or = 2 in 19 (38%) and 17 (34%) patients, respectively. In only one third of the specimens was there any similarity between the 2 types of staining. Advanced tumor stage, high pretreatment PSA levels and high Gleason scores were evenly distributed among the patients with low (< or = 1) and intermediate/high (> or = 2) ErbB-4 expression. The probability of lymph node involvement and 5-year disease free survival were similar in both types of staining. ErbB-4 was overexpressed (cytoplasmic and nuclear staining) in approximately one third of prostate cancer patients. The rate of similarity between the 2 staining types was only 33%: overexpression was evenly distributed among intermediate/high and low risk prostate cancer patients with both staining methods.